Interface-coated solid electrolyte and lithium-ion solid-state battery

By using magnetron sputtering process to set up the LMF interface modification layer of Li-Mg alloy and LiF layer in an all-solid-state lithium-ion battery, the interface problems and dendritic growth problems of lithium metal negative electrodes are solved, and the battery impedance and electrochemistry are improved Performance and effect, simple process and low cost.

CN119481375APending Publication Date: 2025-02-18ZHEJIANG INTELLIGENT TRANSPORTATION TECHNOLOGY INNOVATION CENTER +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411680070.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In all-solid-state lithium-ion batteries, the application of lithium metal negative electrodes has interface problems and dendritic growth problems. The existing solutions are complex or expensive in processes, making it difficult to achieve large-scale production.

Method used

The LMF interface modification layer of the Li-Mg alloy and LiF layer is arranged on the surface of the solid electrolyte by magnetron sputtering process, with a thickness of ≤60nm. The contact resistance between the lithium metal and the electrolyte is improved through the synergistic effect of the Li-Mg alloy and the LiF layer.

Benefits of technology

It effectively reduces the impedance of the interface coated solid electrolyte, improves the electrochemical performance of lithium-ion solid-state batteries, and has a simple process and low cost, which is suitable for industrial-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005148102040000101
    Figure BDA0005148102040000101
  • Figure BDA0005148102040000111
    Figure BDA0005148102040000111
  • Figure BDA0005148102040000112
    Figure BDA0005148102040000112
Patent Text Reader

Abstract

The invention discloses an interface coated solid-state electrolyte and a lithium ion solid-state battery, the interface coated solid-state electrolyte comprises a solid-state electrolyte and an LMF interface modification layer arranged on the surface of the solid-state electrolyte; the thickness of the LMF interface modification layer is smaller than or equal to 60 nm. Through the arrangement of the LMF interface modification layer with the thickness of less than or equal to 60nm, under the synergistic effect of Li-Mg alloy and LiF in the LMF interface modification layer, the contact resistance between lithium metal and the electrolyte is effectively improved, the impedance of the interface-coated solid electrolyte can be effectively reduced by adopting simple and low-cost raw materials and a preparation process, and the interface-coated solid electrolyte has the advantages of low cost and high efficiency. Further, the electrochemical performance of the prepared lithium ion solid-state battery is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of all-solid-state lithium-ion batteries, and in particular to an interface-coated solid electrolyte and a lithium-ion solid-state battery. Background Art

[0002] At present, lithium-ion batteries (LIBs) have attracted more extensive attention due to their greatly improved energy and power density and significantly reduced battery prices; however, LIBs have thermal instability and energy density issues. Among them, the risks and hazards that lead to thermal failure of LIBs are mainly attributed to the flammable organic electrolytes, which lead to safety hazards. The safety issues of LIBs limit their development. Therefore, the use of solid inorganic electrolytes instead of flammable liquid electrolytes can fundamentally prevent thermal runaway. At present, the disclosed all-solid-state batteries (ASSBs) are usually classified according to the raw material type of the solid electrolyte, such as oxide ASSBs, sulfide ASSBs, and polymer ASSBs. Among the different types of ASSBs, sulfide ASSBs are particularly promising due to their high ionic conductivity comparable to that of liquid electrolytes and the good formability of sulfide solid electrolytes.

[0003] Meanwhile, due to the ultra-high specific capacity (3860 mAh / g) and low negative potential of -3.04 V of lithium metal, a lot of research has been conducted in the prior art to replace graphite anode with lithium metal in rechargeable batteries. However, lithium metal is susceptible to unstable side reactions, continuous solid electrolyte interface (SEI) growth and dendrite growth, so the application of lithium metal anode in ASSBs still remains a huge challenge, especially in sulfide-based ASSBs.

[0004] In order to solve the interface problem and dendrite growth problem, in the prior art, a nanostructured lithium selenide (Li2Se) protective layer is epitaxially grown on the lithium metal negative electrode by chemical vapor deposition to improve the chemical stability of lithium metal; or, the controlled reaction of H3PO4 with the lithium metal negative electrode in a tetrahydrofuran solution can form a homogeneous LiH2PO4 protective layer in situ between the lithium metal negative electrode and the LGPS electrolyte; or, a thin Li3PO4 film is introduced on the lithium metal negative electrode to reconstruct the Li / LGPS interface, etc.; however, these interface modification layers usually need to be obtained through complex materials or expensive processes, and cannot be simply and low-costly mass-produced in industrial production. Summary of the invention

[0005] Therefore, the technical problem to be solved by the present invention is that the means used to solve the interface problem and the dendrite growth problem when the lithium metal negative electrode is applied in ASSB have the defects of complex process or high cost, so as to provide an interface-coated solid electrolyte and lithium-ion solid-state battery that can be simply and low-costly mass-produced in industrial production.

[0006] An interface-coated solid electrolyte comprises: a solid electrolyte and an LMF interface modification layer arranged on the surface of the solid electrolyte; the thickness of the LMF interface modification layer is ≤60nm. For example, the thickness of the LMF interface modification layer is any value among 20nm, 21nm, 22nm, 23nm, 24nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 53nm, 55nm, 58nm, 60nm, etc., or a value not shown between any two values.

[0007] The LMF interface modification layer includes a Li-Mg alloy and a LiF layer.

[0008] The LMF interface modification layer is arranged on the surface of the solid electrolyte by using a magnetron sputtering process.

[0009] The target material used in the magnetron sputtering process is MgF2.

[0010] The power of the magnetron sputtering is 90W-110W;

[0011] The magnetron sputtering time is ≤140s.

[0012] The vacuum degree of the magnetron sputtering is ≤5×10 -4 Pa;

[0013] And / or, the sputtering gas pressure of the magnetron sputtering is ≤1Pa;

[0014] And / or, the self-bias voltage of the magnetron sputtering is -720V;

[0015] And / or, the gas source of the magnetron sputtering process includes any one of Ar, He, and Ne.

[0016] Furthermore, the thickness of the LMF interface modification layer is 21nm-55nm.

[0017] The solid electrolyte includes any one of a LATP type solid electrolyte, a LLZO type solid electrolyte, a LLZTO type solid electrolyte, and a LPSC type solid electrolyte.

[0018] A lithium-ion solid-state battery comprises the above-mentioned interface-coated solid-state electrolyte.

[0019] The negative electrode of the lithium-ion solid-state battery is a lithium metal negative electrode.

[0020] The technical solution of the present invention has the following advantages:

[0021] The present invention provides an interface-coated solid electrolyte, comprising a solid electrolyte and an LMF interface modification layer arranged on the surface of the solid electrolyte; the thickness of the LMF interface modification layer is ≤60nm. The present invention eliminates the poor ionic conductivity components introduced by the solid electrolyte|Li interface layer through the constructed mixed conductive Li-Mg / LiF layer (i.e., the LMF interface modification layer); on the one hand, the Li-Mg alloy in the intermediate layer makes the electron distribution more uniform, and at the same time helps to further enhance the chemical contact between Li and the electrolyte and reduce the interface impedance, while LiF, as an electronic insulator, can effectively prevent the occurrence of electron tunneling and further inhibit the nucleation of Li at the electrolyte grain boundary; therefore, by setting the LMF interface modification layer of a specific thickness (≤60nm), under the synergistic effect of the Li-Mg alloy and LiF in the LMF interface modification layer, the contact resistance between the lithium metal and the electrolyte is significantly improved, and the impedance of the interface-coated solid electrolyte can be effectively reduced by using simple, low-cost raw materials and preparation processes, thereby effectively reducing the battery impedance (Ω) of the lithium ion solid-state battery prepared therefrom, and improving the electrochemical performance of the lithium ion solid-state battery. DETAILED DESCRIPTION

[0022] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0024] Example 1

[0025] An interface-coated solid electrolyte, the preparation process of which is as follows:

[0026] Preparation of LPSC type solid electrolyte: weigh three raw materials of Li2S, P2S5 and LiCl with a molar ratio of 5:1:2, crush them in a ball mill for 12 hours, take them out, press the precursor into tablets under a pressure of 150MPa, sinter them at 550℃ in a tubular furnace with Ar for 10 hours, take them out and crush them to a particle size of less than 3um, press the electrolyte material into tablets under a pressure of 150MPa, and polish the surface to obtain LPSC type solid electrolyte.

[0027] Preparation of interface-coated solid electrolyte: MgF2 was used as the target material and LPSC solid electrolyte was used as the substrate. Magnetron sputtering equipment was used in a vacuum of 5×10 -4 The LMF-1 material was obtained by sputtering for 50 s under the conditions of 0.3 Pa, argon partial pressure of 0.7 Pa, sputtering matching power of 100 W and self-bias of -720 V.

[0028] Example 2

[0029] An interface-coated solid electrolyte, the preparation process of which is as follows:

[0030] Preparation of LPSC type solid electrolyte: weigh three raw materials of Li2S, P2S5 and LiCl with a molar ratio of 5:1:2, crush them in a ball mill for 12 hours, take them out, press the precursor into tablets under a pressure of 150MPa, sinter them at 550℃ in a tubular furnace with Ar for 10 hours, take them out and crush them to a particle size of less than 3um, press the electrolyte material into tablets under a pressure of 150MPa, and polish the surface to obtain LPSC type solid electrolyte.

[0031] Preparation of interface-coated solid electrolyte: MgF2 was used as the target material and LPSC solid electrolyte was used as the substrate. Magnetron sputtering equipment was used in a vacuum of 5×10 -4 The LMF-2 material was obtained by sputtering for 70s under the conditions of 0.3 Pa, argon partial pressure of 0.7 Pa, sputtering matching power of 100 W and self-bias of -720 V.

[0032] Example 3

[0033] An interface-coated solid electrolyte, the preparation process of which is as follows:

[0034] Preparation of LPSC type solid electrolyte: weigh three raw materials of Li2S, P2S5 and LiCl with a molar ratio of 5:1:2, crush them in a ball mill for 12 hours, take them out, press the precursor into tablets under a pressure of 150MPa, sinter them at 550℃ in a tubular furnace with Ar for 10 hours, take them out and crush them to a particle size of less than 3um, press the electrolyte material into tablets under a pressure of 150MPa, and polish the surface to obtain LPSC type solid electrolyte.

[0035] Preparation of interface-coated solid electrolyte: MgF2 was used as the target material and LPSC solid electrolyte was used as the substrate. Magnetron sputtering equipment was used in a vacuum of 5×10 -4 The LMF-3 material was obtained by sputtering for 90s under the conditions of 0.3 Pa, argon partial pressure of 0.7 Pa, sputtering matching power of 100 W and self-bias of -720 V.

[0036] Example 4

[0037] An interface-coated solid electrolyte, the preparation process of which is as follows:

[0038] Preparation of LPSC type solid electrolyte: weigh three raw materials of Li2S, P2S5 and LiCl with a molar ratio of 5:1:2, crush them in a ball mill for 12 hours, take them out, press the precursor into tablets under a pressure of 150MPa, sinter them at 550℃ in a tubular furnace with Ar for 10 hours, take them out and crush them to a particle size of less than 3um, press the electrolyte material into tablets under a pressure of 150MPa, and polish the surface to obtain LPSC type solid electrolyte.

[0039] Preparation of interface-coated solid electrolyte: MgF2 was used as the target material and LPSC solid electrolyte was used as the substrate. Magnetron sputtering equipment was used in a vacuum of 5×10 -4 The LMF-4 material was obtained by sputtering for 120s under the conditions of 0.3 Pa, argon partial pressure of 0.7 Pa, sputtering matching power of 100 W and self-bias of -720 V.

[0040] Example 5

[0041] An interface-coated solid electrolyte, the preparation process of which is as follows:

[0042] Preparation of LPSC type solid electrolyte: weigh three raw materials of Li2S, P2S5 and LiCl with a molar ratio of 5:1:2, crush them in a ball mill for 12 hours, take them out, press the precursor into tablets under a pressure of 150MPa, sinter them at 550℃ in a tubular furnace with Ar for 10 hours, take them out and crush them to a particle size of less than 3um, press the electrolyte material into tablets under a pressure of 150MPa, and polish the surface to obtain LPSC type solid electrolyte.

[0043] Preparation of interface-coated solid electrolyte: MgF2 was used as the target material and LPSC solid electrolyte was used as the substrate. Magnetron sputtering equipment was used in a vacuum of 5×10 -4 The LMF-5 material was obtained by sputtering for 70s under the conditions of 0.5 Pa, argon partial pressure of 0.7 Pa, sputtering matching power of 90 W and self-bias of -720 V.

[0044] Example 6

[0045] An interface-coated solid electrolyte, the preparation process of which is as follows:

[0046] Preparation of LPSC type solid electrolyte: weigh three raw materials of Li2S, P2S5 and LiCl with a molar ratio of 5:1:2, crush them in a ball mill for 12 hours, take them out, press the precursor into tablets under a pressure of 150MPa, sinter them at 550℃ in a tubular furnace with Ar for 10 hours, take them out and crush them to a particle size of less than 3um, press the electrolyte material into tablets under a pressure of 150MPa, and polish the surface to obtain LPSC type solid electrolyte.

[0047] Preparation of interface-coated solid electrolyte: MgF2 was used as the target material and LPSC solid electrolyte was used as the substrate. Magnetron sputtering equipment was used in a vacuum of 5×10 -4 The LMF-6 material was obtained by sputtering for 50s under the conditions of 0.677 Pa, argon partial pressure of 0.7 Pa, sputtering matching power of 110 W and self-bias of -720 V.

[0048] Example 7

[0049] An interface-coated solid electrolyte, the preparation process of which is as follows:

[0050] LATP type solid electrolyte: composed of Li 1.3 Al 0.3 Ti 1.7 PO4 is a commercially available finished product, and the specific preparation process will not be described in detail here.

[0051] Preparation of interface-coated solid electrolyte: MgF2 was used as the target material and LATP-type solid electrolyte was used as the substrate. Magnetron sputtering equipment was used in a vacuum of 5×10 -4 The LMF-7 material was obtained by sputtering for 50s under the conditions of 0.3 Pa, argon partial pressure of 0.7 Pa, sputtering matching power of 100 W and self-bias of -720 V.

[0052] Example 8

[0053] An interface-coated solid electrolyte, the preparation process of which is as follows:

[0054] LLZO type solid electrolyte: Among them, zirconium oxide accounts for about 25% of the mass of the raw materials before sintering of LLZO, lanthanum oxide accounts for about 45%, and lithium hydroxide accounts for about 30%. The LLZO type solid electrolyte is prepared by conventional preparation technology.

[0055] Preparation of interface coated solid electrolyte: MgF2 was used as the target material and LLZO solid electrolyte was used as the substrate. Magnetron sputtering equipment was used in a vacuum of 5×10 -4 The LMF-8 material was obtained by sputtering for 50s under the conditions of 0.3 Pa, argon partial pressure of 0.7 Pa, sputtering matching power of 100 W and self-bias of -720 V.

[0056] Example 9

[0057] An interface-coated solid electrolyte, the preparation process of which is as follows:

[0058] Preparation of LLZTO-type solid electrolyte: composition is Li 6.25 Al 0.25 La3Zr2O 12 , which is a finished product purchased, and the specific preparation process will not be repeated here.

[0059] Preparation of interface coated solid electrolyte: MgF2 was used as the target material and LLZTO solid electrolyte was used as the substrate. Magnetron sputtering equipment was used in a vacuum of 5×10 -4 The LMF-9 material was obtained by sputtering for 50s under the conditions of 0.3 Pa, argon partial pressure of 0.7 Pa, sputtering matching power of 100 W and self-bias of -720 V.

[0060] Comparative Example 1

[0061] A solid electrolyte, the preparation process of which is as follows:

[0062] Preparation of LPSC type solid electrolyte: weigh three raw materials of Li2S, P2S5 and LiCl with a molar ratio of 5:1:2, crush them in a ball mill for 12 hours, take them out, press the precursor into tablets under a pressure of 150MPa, sinter them at 550℃ in a tubular furnace with Ar for 10 hours, take them out and crush them to a particle size of less than 3um, press the electrolyte material into tablets under a pressure of 150MPa, and polish the surface to obtain LPSC type solid electrolyte.

[0063] Comparative Example 2

[0064] An interface-coated solid electrolyte, the preparation process of which is as follows:

[0065] Preparation of LPSC type solid electrolyte: weigh three raw materials of Li2S, P2S5 and LiCl with a molar ratio of 5:1:2, crush them in a ball mill for 12 hours, take them out, press the precursor into tablets under a pressure of 150MPa, sinter them at 550℃ in a tubular furnace with Ar for 10 hours, take them out and crush them to a particle size of less than 3um, press the electrolyte material into tablets under a pressure of 150MPa, and polish the surface to obtain LPSC type solid electrolyte.

[0066] Preparation of interface-coated solid electrolyte: MgF2 was used as the target material and LPSC solid electrolyte was used as the substrate. Magnetron sputtering equipment was used in a vacuum of 5×10 -4 The LPSC-1 material was obtained by sputtering for 150 s under the conditions of 0.3 Pa, argon partial pressure of 0.7 Pa, sputtering matching power of 100 W and self-bias of -720 V.

[0067] Comparative Example 3

[0068] An interface-coated solid electrolyte, the preparation process of which is as follows:

[0069] Preparation of LPSC type solid electrolyte: weigh three raw materials of Li2S, P2S5 and LiCl with a molar ratio of 5:1:2, crush them in a ball mill for 12 hours, take them out, press the precursor into tablets under a pressure of 150MPa, sinter them at 550℃ in a tubular furnace with Ar for 10 hours, take them out and crush them to a particle size of less than 3um, press the electrolyte material into tablets under a pressure of 150MPa, and polish the surface to obtain LPSC type solid electrolyte.

[0070] Preparation of interface-coated solid electrolyte: MgF2 was used as the target material and LPSC solid electrolyte was used as the substrate. Magnetron sputtering equipment was used in a vacuum of 5×10 -4 The LPSC-2 material was obtained by sputtering for 200s under the conditions of 0.3 Pa, argon partial pressure of 0.7 Pa, sputtering matching power of 100 W, and self-bias of -720 V.

[0071] Comparative Example 4

[0072] An interface-coated solid electrolyte, the preparation process of which is as follows:

[0073] Preparation of LPSC type solid electrolyte: weigh three raw materials of Li2S, P2S5 and LiCl with a molar ratio of 5:1:2, crush them in a ball mill for 12 hours, take them out, press the precursor into tablets under a pressure of 150MPa, sinter them at 550℃ in a tubular furnace with Ar for 10 hours, take them out and crush them to a particle size of less than 3um, press the electrolyte material into tablets under a pressure of 150MPa, and polish the surface to obtain LPSC type solid electrolyte.

[0074] Preparation of interface-coated solid electrolyte: MgF2 was used as the target material and LPSC solid electrolyte was used as the substrate. Magnetron sputtering equipment was used in a vacuum of 5×10 -4 The LPSC-3 material was obtained by sputtering for 500s under the conditions of 0.3 Pa, argon partial pressure of 0.7 Pa, sputtering matching power of 100 W and self-bias of -720 V.

[0075] Comparative Example 5

[0076] A solid electrolyte, which is the LATP type solid electrolyte in Example 7.

[0077] Comparative Example 6

[0078] A solid electrolyte, which is the LLZO solid electrolyte obtained in Example 8.

[0079] Comparative Example 7

[0080] A solid electrolyte, which is the LLZTO solid electrolyte in Example 9.

[0081] Experimental Example 1

[0082] The solid electrolytes of the above-mentioned embodiments and comparative examples were subjected to quantitative comparison of the thickness of the interface modification layer and solid electrolyte impedance (Ω) detection.

[0083] The impedance (Ω) detection method of the solid electrolyte is: use the VSP electrochemical workstation of Biologic of France to test the impedance of the solid electrolyte, the test disturbance voltage is 10mV, and the frequency range is 1MHZ-10mHZ.

[0084] The test results are shown in Tables 1 to 4 below.

[0085] Table 1

[0086]

[0087] Table 2

[0088]

[0089] Table 3

[0090]

[0091] Table 4

[0092]

[0093] It can be seen from the data in Tables 1 to 4 above that the present invention can effectively reduce the impedance of the interface-coated solid electrolyte by using simple, low-cost raw materials and preparation processes.

[0094] Experimental Example 2

[0095] The solid electrolytes of the above embodiments and comparative examples were assembled into an all-solid-state battery, and the all-solid-state battery was subjected to charge and discharge tests under 0.1C conditions to obtain the battery impedance (Ω), first discharge specific capacity (mAh / g) and capacity retention rate (%) at 100 cycles.

[0096] Among them, the specific process of assembling solid electrolyte into all-solid-state battery is:

[0097] (1) Preparation of positive electrode sheet: 8g of positive electrode active material NCM955, 1.65g of solid electrolyte Li6PS5Cl, 0.2g of binder polyvinylidene fluoride (PVDF) and 0.15g of conductive agent vapor-grown carbon fiber (VGCF) are added to 10mL of solvent xylene and stirred. For example, in an environment where the dew point temperature is less than 50°C, the stirrer is stirred at a constant speed of 500rpm for 5 hours to obtain a slurry. The above-prepared slurry is coated on the current collector aluminum foil, and then dried in an oven at 90°C for 12 hours. The dew point temperature of the environment in which the electrode sheet is located should be kept below 50°C during the drying process, or nitrogen should be filled in this environment for protection. After the organic solvent in the electrode sheet is completely evaporated, the electrode sheet is cooled to room temperature and taken out of the oven to obtain a finished positive electrode sheet.

[0098] (2) Preparation of negative electrode sheet: 7g of negative electrode active material graphite, 2.65g of solid electrolyte Li6PS5Cl, 0.2g of binder polyvinylidene fluoride (PVDF) and 0.15g of conductive agent vapor-grown carbon fiber (VGCF) are added to 10mL of solvent xylene and stirred. For example, in an environment where the dew point temperature is less than 50°C, the stirrer is stirred at a constant speed of 500rpm for 5 hours to obtain a slurry. The above-prepared slurry is coated on the current collector copper foil, and then dried in an oven at 90°C for 12 hours. The dew point temperature of the environment in which the electrode sheet is located should be kept below 50°C during the drying process, or nitrogen should be filled in this environment for protection. After the organic solvent in the electrode sheet is completely evaporated, the electrode sheet is cooled to room temperature and taken out of the oven.

[0099] (3) Battery assembly: Under a pressure of 100 MPa, the interface-coated solid electrolyte is transferred to the surface of the positive electrode sheet, and then the negative electrode sheet is placed close to the interface-coated solid electrolyte. The finished product is pressed at a pressure of 500 MPa and encapsulated with an aluminum-plastic film to obtain a finished battery.

[0100] The battery impedance (Ω) detection method is: use the French Biologic's VSP electrochemical workstation to test the interface impedance of the solid-state battery. The test disturbance voltage is 10mV and the frequency range is 1MHZ-10mHZ.

[0101] The test results are shown in Table 5 below.

[0102] Table 5

[0103]

[0104]

[0105] It can be seen from the above data of the embodiments and comparative examples that the sputtering LMF interface modification layer reduces the interface impedance of the electrolyte and effectively improves it. However, when the thickness of the LMF interface modification layer reaches the optimum, the thicker the thickness, the greater the interface impedance. When the thickness increases to more than 60nm, the interface impedance will be greater than that without the LMF interface modification layer. Therefore, the thickness of the LMF interface modification layer of the present invention is ≤60nm. It can be seen from the thickness data of the embodiments that when the thickness of the LMF interface modification layer reaches between 21nm-55nm, the interface impedance can be significantly reduced. When the thickness reaches about 25nm, it shows the smallest impedance and the highest first discharge capacity. After 100 cycles, the capacity retention rate can still reach 95.6%, and the effect is significant.

[0106] Moreover, the process method of the present invention is simple and efficient, non-toxic and pollution-free, does not contain any organic and inorganic reagents, and is environmentally friendly and pollution-free; at the same time, there is no material loss during the treatment process, the output can reach 100%, and the cost is reduced.

[0107] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. An interface-coated solid electrolyte, characterized in that: It comprises a solid electrolyte and a LMF interface modification layer arranged on the surface of the solid electrolyte; the thickness of the LMF interface modification layer is ≤60nm.

2. The interface-coated solid electrolyte according to claim 1, characterized in that: The LMF interface modification layer is arranged on the surface of the solid electrolyte by using a magnetron sputtering process.

3. The interface-coated solid electrolyte according to claim 2, characterized in that: The target material used in the magnetron sputtering process is MgF2.

4. The interface-coated solid electrolyte according to claim 2, characterized in that: The power of the magnetron sputtering process is 90W-110W.

5. The interface-coated solid electrolyte according to claim 2, characterized in that: The sputtering time of the magnetron sputtering process is ≤140s.

6. The interface-coated solid electrolyte according to any one of claims 2 to 5, characterized in that: The vacuum degree of the magnetron sputtering process is ≤5×10 -4 Pa; And / or, the sputtering gas pressure of the magnetron sputtering process is ≤1Pa; And / or, the self-bias voltage of the magnetron sputtering process is -720V; And / or, the gas source of the magnetron sputtering process includes any one of Ar, He, and Ne.

7. The interface-coated solid electrolyte according to any one of claims 1 to 5, characterized in that: The thickness of the LMF interface modification layer is 21nm-55nm.

8. The interface-coated solid electrolyte according to any one of claims 1 to 5, characterized in that: The solid electrolyte includes any one of a LATP type solid electrolyte, a LLZO type solid electrolyte, a LLZTO type solid electrolyte, and a LPSC type solid electrolyte.

9. A lithium-ion solid-state battery, characterized in that: It comprises the interface-coated solid electrolyte according to any one of claims 1 to 8.

10. The lithium-ion solid-state battery according to claim 9, characterized in that: The negative electrode of the lithium-ion solid-state battery is a lithium metal negative electrode.